Given:
The graphs of two parabolas.
To find:
The equation of the quadratic function with given graphs.
Solution:
(a)
The factor form of a parabola is
![y=a(x-b)(x-c)](https://img.qammunity.org/2022/formulas/mathematics/high-school/nvliz8d6c9r17pfr36x5j9hnnqma6yp7zq.png)
Where, a is a constant, b and c are x-intercepts.
From the graph (a) it is clear that the graph intersect the x-axis at -1 and 3. So, b=-1 and c=3.
![y=a(x-(-1))(x-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/15ysrr9o3gw6d7hr5diavxh1oei4hovbts.png)
...(i)
Put x=0 and y=3 because the y-intercept is (0,3).
![3=a(0+1)(0-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/snywbbh5xh573va4oe1rryv84ldehcqq65.png)
![3=-3a](https://img.qammunity.org/2022/formulas/mathematics/high-school/iye8h2c3lyh15tqk0mneli6ykg75jkx87k.png)
![(3)/(-3)=a](https://img.qammunity.org/2022/formulas/mathematics/high-school/k5g7m22cfj0kee3t2zythuhiwpoa557yws.png)
![-1=a](https://img.qammunity.org/2022/formulas/mathematics/high-school/8pjmnngmpjn31oa9h9l7gq9rnu6fz2o1l8.png)
Putting a=-1 in (i), we get
![y=-1(x+1)(x-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/tvheu1xvuz254ptbxlpflllywwfbdmim8k.png)
![y=-(x+1)(x-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/b7mz5ivtcs0yoyvi913x4eqloxogxb0awq.png)
Therefore, the equation of the parabola is
.
(b)
The vertex form of a parabola is
![y=a(x-h)^2+k](https://img.qammunity.org/2022/formulas/mathematics/high-school/2ksh02tid7iqrs7hbao6per7xmvpd7m949.png)
Where, a is a constant and (h,k) is vertex.
From the the graph (b), it is clear that the vertex of the of the parabola is at point (2,0) and y-axis is (0,8). So, h=2, k=0.
![y=a(x-2)^2+0](https://img.qammunity.org/2022/formulas/mathematics/high-school/rznr9eqek3tt3m9qaeindlqo06hetdo5sz.png)
...(ii)
Put x=0 and y=8 because the y-intercept is (0,8).
![8=a(0-2)^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/9vxhaefnssbi52c2vf8n1c7zmkrku6nsnl.png)
![8=4a](https://img.qammunity.org/2022/formulas/mathematics/high-school/3c200qtxp5q635rl3a1sn87skbvjg9ziw3.png)
![(8)/(4)=a](https://img.qammunity.org/2022/formulas/mathematics/high-school/z3nr7cjtfbwms7kmumrg756fwtdooapn8d.png)
![2=a](https://img.qammunity.org/2022/formulas/mathematics/high-school/fb5i0aih1444snxq3qz3pxv2jhogtxhe4i.png)
Putting a=2 in (ii), we get
![y=2(x-2)^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/bwtxtft265jdhlrr2tu2gtsaxfftj297lg.png)
Therefore, the equation of the parabola is
.